Diversity and vertical distributions of scarabaeids dungbeetles (Coleoptera: Scarabaeidae) in the tropical mountaineous rainforest of Gede Pangrango National Park, West Java, Indonesia - SIH KAHONO; LILIK KUNDAR SETIADI (Society for Indonesian Biodiversity, 2007)
Diversity and vertical distributions of scarabaeids dungbeetles (Coleoptera: Scarabaeidae) were studied in a tropical mountaineous rainforest of Gede Pangrango National Park using dung traps. Samples were collected at four altitudes of 500-1000m, 1001-1500, 1501- 2000, and 2001-2500m of five different collection sites (Cibodas, Selabintana, Situ Gunung, Bodogol, and Gunung Putri). 1052 individuals of 28 species of scarabaeid dungbeetles that belongs to five genus were collected. The most diverse groub was the genus Onthophagus, which consists of 21 species (75% of collected species) and followed by Copris with 3 species (10.7%), Paragymnopleurus with 2 species (7.1%), Catarsius with 1 species (3.6%), and Phacosoma with 1 species (3.6%). The Shanon-Winner index of diversity and evenness were gradually declining during the time when altitudes were increasing. Altitude was an important factor in the diversity, abundance, and distribution of dungbeetles. The diversity of dungbeetles at the interval of 1001-1500m and 1501-2000m were not so high but abundance and similarity were high. Diversity index, evenness, abundance, and species similarity of dungbeetles at the interval of 2001-2500m was low because of unfavourable habitat. Although the diversity of dungbeetles at the interval 500-1000m was the highest, however abundance and similarity index were relatively low. Analyse of diversity, abundance, evenness, and similarity of dungbeetles on each of the different altitudes and environment conditions were discussed in this paper.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: diversity, vertical distributions, scarabaeid dungbeetles, Gede Pangrango National Park, Wawonii Island.